PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Vera Helmalia Putri; Savitri Suryandari; Mahyuni Rahayu (CV. Adiba Aisha Amira, 2025)
Based on interviews and observations that have been made to teachers and third grade students of SDN Pakis 1 Surabaya, there are problems found in learning activities in the form of a lack of variety of learning activities which have an impact on student learning outcomes below the predetermined KKTP. The purpose of this study was to improve student learning outcomes through the application of the Team Games Tournament (TGT) learning model. The method used in this research is Classroom Action Research (PTK) which is carried out in 2 research cycles with data collection techniques in the form of observation, interviews, tests, and documentation. The increase in student learning outcomes in cycle I was 64.28% and experienced a significant increase in cycle II of 89.285.